Assessment of N Mineralization and N Leaching in Soil Using a New in situ Incubation Method. Issue 19 (27th October 2016) - Sousa, J. R.; Cabral, F.; Coutinho, J.
ABSTRACT: Field incubations have been pointed out as the more realistic method to provide estimates of nitrogen (N) mineralization. The aim of this study is to evaluate the quality of the results obtained in a field incubation using an open reactor to estimate net N mineralization and N leaching. The incubation experiment was initiated with 24 reactors. At each date, the reactors were destructed and mineral N in the soil and adsorbed on the exchange resins was determined. Net N mineralization and N leaching were estimated as 23.3 and 18.0 mg/kg, respectively. The results revealed an acceptable repeatability, with coefficient of variation (CV) of 9.0%, a significant adjustment ( r 2  = 0.991), and a low root mean square error ( Syx  = 4.2) for the regression model used. The use of this type of reactor may be considered as a reliable alternative to assess N mineralization kinetics from native organic matter and probably for organic residues applied to soils in field studies.